Children with cochlear implants and autism – challenges and outcomes: The experience of the National Cochlear Implant Programme, Ireland. (September 2013) - Robertson, Jennifer
<x content-type="archive" xml:space="preserve">Abstract</x> As cochlear implantation (CI) becomes the treatment of choice for many children with severe-profound sensori-neural hearing loss, more children with significant additional special needs become CI recipients. By the end of 2011 3.1% of the children with cochlear implants attending the National Cochlear Implant Programme in Ireland also had a diagnosis of autistic spectrum disorder (ASD). This paper presents a review of the outcomes for these children, with an emphasis on processor use and mode of communication. A more detailed case study for one particular child is also outlined.